From Product-Oriented Learning to Exhibition-Based Exam in Translation Class - Magfirah Thayyib (Pusat Studi Bahasa dan Publikasi Ilmiah, 2023)
Foreign language learners need to be provided with various real experiences to enhance their translation competence. The combination of product-oriented learning and exhibition-based exam is initialized through this research as an attempt to meet the need for translation learning. This research aims to elaborate on the application of product-oriented learning and exhibition-based exam in the translation class. This research was a descriptive study. The data of the research were mostly responses to the activities so a triangulation of quantitative data and qualitative data was employed. The quantitative data were obtained from the students’ questionnaire on the application of product-oriented learning in translation class and the visitors’ questionnaire on exhibition-based exam at the end of the course. Whilst, the qualitative data were taken from the lecturer’s observation notes. The research results show that the students had attained knowledge and skill in translation, entrepreneurial training, and enjoyment in learning. The students also gave positive responses toward the application of product-oriented learning and exhibition-based exam in translation class. The results proved that product-oriented learning and exhibition-based exam are compatible. The gist of exhibition-based exam supports the goal and process of product-oriented learning.